2011
DOI: 10.1111/j.1574-6941.2011.01204.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of long-term fertilization of forest soils on potential nitrification and on the abundance and community structure of ammonia oxidizers and nitrite oxidizers

Abstract: Forest fertilization in British Columbia is increasing, to alleviate timber shortfalls resulting from the mountain pine beetle epidemic. However, fertilization effects on soil microbial communities, and consequently ecosystem processes, are poorly understood. Fertilization has contrasting effects on ammonia-oxidizing bacteria and archaea (AOB and AOA) in grassland and agricultural ecosystems, but there are no studies on AOB and AOA in forests. We assessed the effect of periodic (6-yearly application 200 kg N h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
74
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(93 citation statements)
references
References 56 publications
13
74
6
Order By: Relevance
“…For example, in two acidic forest soils that long suffered from a heavy load of N deposition dominated by dry N deposition and acid deposition, it was found that nitrification in organic and 0-10 cm mineral soils was dominated by heterotrophic nitrification (Jordan et al 2005). However, Wertz et al (2012) reported that autotrophic nitrification still contributed mostly (54.6 to 96.9 %) to nitrification in N-amended organic and mineral soils of lodgepole pine and spruce stands. However, to our knowledge, research on specific pathway-related processes such as autotrophic nitrification and heterotrophic nitrification in N-deposited and N-fertilized forest sites is still very lacking (Tables 1 and 2).…”
Section: Nitrificationmentioning
confidence: 92%
See 2 more Smart Citations
“…For example, in two acidic forest soils that long suffered from a heavy load of N deposition dominated by dry N deposition and acid deposition, it was found that nitrification in organic and 0-10 cm mineral soils was dominated by heterotrophic nitrification (Jordan et al 2005). However, Wertz et al (2012) reported that autotrophic nitrification still contributed mostly (54.6 to 96.9 %) to nitrification in N-amended organic and mineral soils of lodgepole pine and spruce stands. However, to our knowledge, research on specific pathway-related processes such as autotrophic nitrification and heterotrophic nitrification in N-deposited and N-fertilized forest sites is still very lacking (Tables 1 and 2).…”
Section: Nitrificationmentioning
confidence: 92%
“…For instance, in acidic forest soils of southern China, low soil pH led to the low rate of autotrophic nitrification (Zhang et al 2013a). Despite the fact that Wertz et al (2012) found that fertilization increased the abundances of AOB and Nitrobacter-like NOB, rather than ammoniaoxidizing archaea (AOA) and Nitrospira-like NOB abundances, there is increasing evidence that AOA, with a higher affinity for low concentrations of NH 3 in acidic environment, leads to AOB in ammonia oxidation in acidic forest soils (Levy-Booth et al 2014;Zhang et al 2012b). However, rates of autotrophic nitrification in acidic forest soils are generally reported to be low even in the case of N input (Schmidt et al 2007;Zhang et al 2013a).…”
Section: Nitrificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have revealed that long-term fertilisation, whether balanced or unbalanced, influences both the abundance and composition of the soil microbial community (Wu et al, 2011;Wertz et al, 2012). Because the enzymes in the soil originate mainly from these microorganisms, our hypothesis was that balanced or unbalanced long-term fertilisation could alter the specific activity and kinetic parameters of oxidoreductases to differing degrees.…”
Section: Introductionmentioning
confidence: 99%
“…For each pan, one tube was prepared and treated with 50 mg NH 4 -N kg (1 soil as described above, and incubated for 19 d. At the end of the incubation, a subsample of soil from each tube was then used in the nitrification potential assay to represent soils which has been recently exposed to an addition of NH ' 4 : At that time, subsamples of soil were also collected from each pan, which had been maintained at constant water content and 258C in the growth room, to represent soils that did not have exposure to a recent addition of NH ' 4 : Nitrification potential was assayed under aerobic and non-limiting N substrate conditions, using a soil slurry method (Hart et al 1994;Wertz et al 2011) adjusted to account for pH differences among soil samples. To remove any NO 3 ( initially present in the sample, 3 g of soil was shaken with 30 mL potassium phosphate buffer (1 mM, pH 7.2) for 15 min.…”
mentioning
confidence: 99%